2020
DOI: 10.1039/c9ta10471b
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a tunable defect structure in TiO2 for photocatalytic nitrogen fixation

Abstract: This study provides new insights into constructing efficient nitrogen-fixing photocatalysts by optimizing the OV concentration to coordinate the charge separation efficiency and dissociative adsorption capacity of N2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 31 publications
0
68
0
Order By: Relevance
“…A recent example, Zhang and his coworkers demonstrated that the excess of OVs in TiO 2 increased the adsorption and activation ability of N 2 molecules, but also showed disappointing activity due to the decrease of charge separation efficiency. 74 Excess OVs will become the recombination centers of photocarriers, which will greatly Fig. 7 Schematic illustration of the photocatalytic N 2 fixation model in which water serves as both the solvent and proton source, as well as the reversible creation of light-induced Ovs.…”
Section: Oxygen Vacancymentioning
confidence: 99%
“…A recent example, Zhang and his coworkers demonstrated that the excess of OVs in TiO 2 increased the adsorption and activation ability of N 2 molecules, but also showed disappointing activity due to the decrease of charge separation efficiency. 74 Excess OVs will become the recombination centers of photocarriers, which will greatly Fig. 7 Schematic illustration of the photocatalytic N 2 fixation model in which water serves as both the solvent and proton source, as well as the reversible creation of light-induced Ovs.…”
Section: Oxygen Vacancymentioning
confidence: 99%
“…Inspired by this work, Zhang et al have studied the effect of oxygen vacancy concentration on the activity of N 2 fixation by using defect-engineered anatase TiO 2 , which synthesized by a solid phase reduction with NaBH 4 , as a model catalyst. [91] They founded that the sample with optimized oxygen vacancy concentration exhibits a threefold increase in charge separation efficiency and shows enhanced activation ability for N 2 molecules. As a result, a high N 2 photofixation rate of 324.86 µmol g -1 h -1 can be achieved under full spectrum, which is 3.85 times that of pristine anatase TiO 2 .…”
Section: Defect Engineeringmentioning
confidence: 99%
“…[23] Subsequently, many studies have shown that N 2 chemisorption occurs on OV sites of TiO 2 , which is mainly caused by electron transfer from OVs into the antibonding orbital of N 2 when absorbed on OV sites. [9,12] Due to the high specific surface area and significantly improved charge separation efficiency, its 2D structure has been constructed for efficient photocatalytic N 2 RR. Most importantly, the ultrathin structure of 2D TiO 2 exposes more OVs sites on the edge, which is conducive to the adsorption and activation of N 2 molecules.…”
Section: Tiomentioning
confidence: 99%